Reverse Logistics Analysis of Chips Products Towards Green Supply Chain Management in MSMEs - Meilenda, Poppy; Syarif, Amirudin (Yayasan Sinergi Kawula Muda, 2024)
The food industry has the nature of perishable goods, so there is always the possibility of products being returned to the manufacturer, namely reverse logistics. Reverse logistics include collection, sorting, recycling, redistribution, and disposal. One of the main challenges MSMEs face is accumulating unsold or damaged products. Chip products not sold out in the stores where they are kept often have to be recalled, resulting in a buildup of products in the warehouse. This study aims to analyze the practice of reverse logistics of banana chip products in one MSME called A3 and evaluate the extent to which they are based on Green Supply Chain Management (GSCM). The research method used is descriptive qualitative; data collection is done through interviews, direct observation, and analysis of related documents. The results showed that A3 had implemented reverse logistics practices by considering environmental aspects such as production waste management. However, some areas can still be improved further to maximize the contribution to Green Supply Chain Management. The implication of this study is to provide a deeper understanding of reverse logistics practices in the context of MSMEs and provide recommendations for other MSMEs to improve the conformity of their practices with the concept of Green Supply Chain Management.